الرقابة المالية على ميزانية الجماعات المحلية - مختاري عالية; مراح فتيحة; بوجلال أحمد (جامعة عمار ثليجي الاغواط, 2022)
This study aimed at fiscal control of the budget of local communities. The important role of local communities, which are an integral part of the State, plays an important role in ensuring citizens' needs and achieving inclusive development. Local groups that were financially independent and therefore disposal of leadership individually and properly do not restrict control over revenue recruitment and expenditure implementation.